Antioxidant capacity of commercial cranberry juices before and after storage at low temperature - Díaz-Torres, Rocío del Carmen; Cilia-López, Virginia Gabriela (CIENCIA ergo-sum, 2022)
This study evaluated the antioxidant activity (AA) of cranberry juices available in supermarkets of San Luis Potosí, México, before and after storage at low temperature (4°C) by ABTS • , DPPH • , and FRAP methods. Twelve commercial juices were tested at the time of opening (D1) and 24 hours later (D2). The results were expressed as vitamin C equivalent antioxidant capacity (VCEAC) and percentages of free radical inhibition. The highest AA was recorded at 60 min, although it was different in the three methods. The AA decreased significantly in D2. Therefore, our study recommends the consumption of cranberry juice once the container is opened, to ensure the consumption of the antioxidant compounds associated with a beneficial effect on health.